"Transfer" of power: The intersection of DNA virus infection and tRNA biology. (15th September 2023) - Dremel, Sarah E.; Jimenez, Ariana R.; Tucker, Jessica M.
Abstract: Transfer RNAs (tRNAs) are at the heart of the molecular biology central dogma, functioning to decode messenger RNAs into proteins. As obligate intracellular parasites, viruses depend on the host translation machinery, including host tRNAs. Thus, the ability of a virus to fine-tune tRNA expression elicits the power to impact the outcome of infection. DNA viruses commonly upregulate the output of RNA polymerase III (Pol III)-dependent transcripts, including tRNAs. Decades after these initial discoveries we know very little about how mature tRNA pools change during viral infection, as tRNA sequencing methodology has only recently reached proficiency. Here, we review perturbation of tRNA biogenesis by DNA virus infection, including an emerging player called tRNA-derived fragments (tRFs). We discuss how tRNA dysregulation shifts the power landscape between the host and virus, highlighting the potential for tRNA-based antivirals as a future therapeutic.